2017
DOI: 10.1038/nchembio.2346
|View full text |Cite
|
Sign up to set email alerts
|

AtaT blocks translation initiation by N-acetylation of the initiator tRNAfMet

Abstract: This is a repository copy of AtaT blocks translation initiation by N-acetylation of the initiator tRNAfMet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
107
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(109 citation statements)
references
References 52 publications
2
107
0
Order By: Relevance
“…The GNAT superfamily proteins are widely distributed in eukaryotes and prokaryotes, and have been shown to influence many physiological events by transferring the acetyl group from AcCoA to different substrates (Xie et al ., ). Three examples of GNAT toxins have been described, namely TacT of Salmonella enterica Typhimurium (Cheverton et al ., ), AtaT of enterohemorrhagic Escherichia coli O157:H7 (Jurėnas et al, ) and GmvT of Shigella flexneri pINV plasmids (McVicker and Tang, ). The toxicity of these GNAT toxins is abolished by the co‐expression of their cognate antitoxins that contain the ribbon‐helix‐helix (RHH) conserved domains and form the GNAT‐RHH family of type II TA systems.…”
Section: Introductionmentioning
confidence: 99%
“…The GNAT superfamily proteins are widely distributed in eukaryotes and prokaryotes, and have been shown to influence many physiological events by transferring the acetyl group from AcCoA to different substrates (Xie et al ., ). Three examples of GNAT toxins have been described, namely TacT of Salmonella enterica Typhimurium (Cheverton et al ., ), AtaT of enterohemorrhagic Escherichia coli O157:H7 (Jurėnas et al, ) and GmvT of Shigella flexneri pINV plasmids (McVicker and Tang, ). The toxicity of these GNAT toxins is abolished by the co‐expression of their cognate antitoxins that contain the ribbon‐helix‐helix (RHH) conserved domains and form the GNAT‐RHH family of type II TA systems.…”
Section: Introductionmentioning
confidence: 99%
“…Toxins from Salmonella Typhimurium were shown to inhibit translation through acetylation of multiple elongator aminoacyl-tRNAs (12,13). Another translational inhibitor, the AtaT toxin from Escherichia coli O157:H7, was shown to specifically acetylate the amino group of initiator Met-tRNA fMet preventing its interaction with IF2·GTP (14,15). Toxicity of several other GNAT type II toxins has been demonstrated although their actual targets remain unknown (12,14,16–20).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed molecular mechanism of action was reported for two of these GNAT‐toxins, AtaT from E. coli (Jurėnas et al ., a) and TacT from Salmonella enterica serovar Typhimurium (Cheverton et al ., ). An earlier report of another GNAT toxin, GmvT from a virulence plasmid of Shigella sonnei , only showed that it blocks mRNA translation in an acetyl‐CoA‐dependent manner (McVicker and Tang, ).…”
Section: Gnat Toxins: a Newly Discovered Member Of Type II Ta Toxins mentioning
confidence: 97%
“…Even though type II TA toxins were shown to have various molecular targets in the cell including DNA replication and peptidoglycan synthesis, the majority of them appear to affect translation with almost every step of the translation process a target (Table ) (Page and Peti, ; Van Melderen et al ., ). It was suggested that toxins targeting translation may be preferentially selected during evolution as inhibition of protein synthesis could be less harmful when compared to toxins that target DNA replication or peptidoglycan synthesis (Guglielmini and Van Melderen, ; Jurėnas et al ., b).…”
Section: A Multitude Of Type II Toxin–antitoxin (Ta) Systems In Prokamentioning
confidence: 98%
See 1 more Smart Citation